Metabotropic glutamate receptor 3 activation prevents nitric oxide induced death in cultured astrocytes - Durand, Daniela Elizabeth (2009)
Altered glial function may contribute to the initiation or progression of neuronal death in neurodegenerative diseases. Thus, modulation of astrocyte death may be essential for preventing pathological processes in the CNS. In recent years, metabotropic glutamate receptor (mGluR) activation has emerged as a key target for neuroprotection. We investigated the effect of subtype 3 mGluR (mGluR3) activation on nitric oxide (NO)-induced astroglial death. A mGluR3 selective agonist, LY379268, reduced inducible NO synthase expression and NO release induced by bacterial lipopolysaccharide and interferon-c in cultured rat astrocytes. In turn, a NO donor (diethylenetriamine/NO) induced apoptotic-like death in cultured astrocytes, which showed apoptotic morphology and DNA fragmentation, but no caspase 3 activation. LY379268 prevented astrocyte death induced by NO exposure, which correlates with a reduction in: phosphatidylserine externalization, p53 and Bax activation and mitochondrial permeability. The reported effects of LY379268 were prevented by the mGluR3 antagonist (s)-a-ethylglutamic acid. All together, these findings show the protective effect of mGluR3 activation on astroglial death and provide further evidence of a role of these receptors in preventing CNS injury triggered by several inflammatory processes associated with dysregulated NO production.